Knowledge, attitude, and practice of psoriatic arthritis among patients with psoriasis - Mei, Aihua; Luan, Mei; Li, Pan; Chen, Jun; Mou, Kuanhou (Frontiers in Medicine, 2024)
Introduction: This study aimed to investigate the knowledge, attitude and practice (KAP) of psoriatic arthritis among patients with psoriasis. The KAP questionnaire is a widely used tool in public health research, designed to assess individuals' understanding (knowledge), beliefs (attitude), and behaviors (practice) related to a specific health condition.A cross-sectional study was conducted at Sinopharm Dongfeng General Hospital from September to November 2023. Demographic information and KAP scores were assessed using a structured questionnaire, which evaluated patient knowledge about psoriatic arthritis, their attitude toward managing it, and their practical engagement in preventive or treatment behaviors.Results: In this study, 392 valid questionnaires were analyzed. Of these, 290 respondents (74.0%) were male, and 296 (75.5%) reported no comorbid conditions. The median scores for knowledge, attitude, and practice were 8 (interquartile range [IQR]: 6-10), 21 (IQR: 19-24), and 14 (IQR: 8-22), respectively. Multivariate logistic regression analysis indicated that practice was independently associated with being female (OR = 0.426, 95% CI: 0.259-0.703, P = 0.001), being aged 30-39 years (OR = 2.159, 95% CI: 1.223-3.811, P = 0.008) or 40-49 years (OR = 2.002, 95% CI: 1.019-3.936, P = 0.044), having a Dermatology Life Quality Index (DLQI) score of 11-30 (OR = 2.569, 95% CI: 1.158-5.700, P = 0.020), and not having psoriatic arthritis (OR = 0.300, 95% CI: 0.168-0.537, P < 0.001).Patients with psoriasis had suboptimal knowledge, positive attitude and inactive practice towards psoriatic arthritis. To address this, healthcare providers should prioritize educational interventions, with a specific focus on younger patients, females, and individuals with a higher DLQI score, to enhance awareness and promote proactive management of psoriatic arthritis among this patient population.